An investigation of direct and indirect learning strategies in learning foreign languages - Seng, Hui Zanne; Che Mustafa, Norliza; Abdul Halim, Hazlina; Rahmat, Noor Hanim; Khairul Amali, Nurul Amirah (Human Resource Management Academic Research Society, 2023)
Learning strategies are one of the multiple factors in accomplishing learners' objectives in acquiring a new language. Hence, the aim of this research is to investigate the strategies that language learners use during their language-learning process. The instrument for this quantitative research is a survey. It has three sections. The first section consists of 2 items on demographic profile, while the second section has 19 items on direct learning strategies. The last section has 22 items on indirect learning strategies. The respondents are 132 undergraduate students taking French as a third language at one of the public universities in Malaysia. The data collected from the respondents were then analyzed using SPSS. The findings show that rehearsal has the highest mean (3.8), but critical thinking has the lowest (3.5). The research also reveals that the help-seeking strategy has the highest mean (4.1), whereas the metacognitive self-regulation strategy has the lowest mean (3.5). From the correlation analysis, the research also indicates a significant association between direct and indirect strategies (r=.779**) and (p=.000). In other words, this research proves that there is a strong relationship between direct strategies (which consist of rehearsal, organization, elaboration and critical thinking strategies); and indirect strategies (metacognitive self-regulation and resource management strategies) in foreign language learning. For future research, it is beneficial to determine if the gender of the learners influences the choice of learning strategies, as this would allow instructors to refine and alter their teaching approaches according to their audience.